Wave-motif on porch railing, Fairlawn - Ayan Ghosh (2023)
Wave motif on porch railing of the compound wall, Fairlawn. A remarkable feature of the Art Deco buildings along Maharshi Karve Marg is the uniformity of form and design. For example, the use of porch railings is common in all the buildings, and they all have a low compound wall running along the front of the building.